150k views
2 votes
3 (n - 5) - (6 -2n) = 4n

2 Answers

3 votes

Answer:

21

Explanation:

3n - 15 - 6 + 2n = 4n

3 n + 2n = 4n + 15 + 6

5 n - 4n = 15 + 6

n = 21

User Sparko Sol
by
6.0k points
4 votes

Answer:

n = 21

Explanation:

Use distributive rule: a(b + c) = a*b + a*c

3(n -5) - (6 - 2n) = 4n

3*n - 3*5 + 6*(-1) - 2n *(-1) = 4n

3n - 15 - 6 + 2n = 4n {add like term in LHS}

3n + 2n - 15 - 6 = 4n

5n - 21 = 4n {add 21 to both sides}

5n -21 + 21 = 4n +21

5n = 4n + 21 {subtract 4n from both sides}

5n - 4n = 4n -4n +21

n = 21

User Fabian Amran
by
5.7k points